(untitled) (Journal of the College of Education for Women, 2019)
One of topics that occupied alarge area in Iraqi society at the moment is the issue( of tribal separation and its relation to the organization of the community ) so we see in the civilizations and heritage of each community aset of provisions and laws that take the form of status customary or religious it is indicative of the great interest in Iraqi society in cotrolling the behavior of individuals to comply with values and social laws and become their behavior is consistent with the behavior of the total and adhere to the social values and be productive individuals within the subject and this can only be achieved from the social control of the various studies have been to emphasize the rol of informal controls in Iraqi society including the tribal separation Customary and some of the lagal in take side and others covered from the religious side therefore the present study came to shed light on the subject from its different dimensions accoding to its previous variables religion and clan and law the study included two main aspects the first aspects the theoretical side of the study it included four chapters that included the first chapter the first section deal with the general framework of the study to clarify the problem of the study and the importance of the study and the objectives of the study social organization community culture social control the second chapter where the first section included previous studies in the fild of tribal separation to benefit from the methods and tools and results the second section included some theories explain the employment those theories in the interpretation of the separation of tribal clan and tribe As for the the third chapter the clan and the social construction includedtwo topics the first is the clan as asocial structure and the second is the clan and the social patterns it highlighted the most prominent social patterns it highlighted the most prominent social patterns in Iraqi society The fourth chapter of the clan as social control group included the first section of the organization of the clan the Role of the clan in the Settlement of Triblal Disputes the second topic is the active forces in the local community and included the role of central governments , the role of local councils ,the role of civil society organizationsand the nature of the local community and its characteristic the second aspect ,the field aspect of the study where the four chapter of the fifth chapter included the scientific and methodological procedures for the study includeding the methodologica used in the study and how to choose the type of research and procedures for verifying the truthfulness of the tool And stability and statistical means used in chapter six where the three topics included the first topic analysis of demographic data and the second study analysis of the data on the axes of the study the third topic analysis of the results of the study ,Chapter VII the three aspects of the first topic included the relationship between variables His variables adopted either the second topic included the terms of reference of social control informal study in the community either third section included some of the case studies models , the eighth chapter included the results